2013
DOI: 10.1007/s00704-013-0935-8
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for two abrupt warming events of SST in the last century

Abstract: We have recently suggested that the warming in the sea surface temperature (SST) since 1900, did not occur smoothly and slowly, but with two rapid shifts in 1925/1926 and 1987/1988, which are more obvious over the tropics and the northern midlatitudes. Apart from these shifts most of the remaining SST variability is due to the El-Nino Southern Oscillation (ENSO) and the Pacific Decadal Oscillation (PDO). Here we provide evidence that the time separation between these two SST shifts (around 60 years) is almost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(14 citation statements)
references
References 54 publications
(30 reference statements)
2
12
0
Order By: Relevance
“…For both LST and SST, the evidence for shifts in other decades is limited. Our analyses confirm earlier findings that SST has increased in steps over the last century (Reid & Beaugrand, 2012;Varotsos et al, 2013) and that the pronounced upward trend in global combined land and sea temperatures seen in the decadal means of Figure SPM.1 in the IPCC Summary for Policy Makers (IPCC SPM, 2013; see also Fig. S4) started in the 1980s.…”
Section: (G)supporting
confidence: 89%
See 1 more Smart Citation
“…For both LST and SST, the evidence for shifts in other decades is limited. Our analyses confirm earlier findings that SST has increased in steps over the last century (Reid & Beaugrand, 2012;Varotsos et al, 2013) and that the pronounced upward trend in global combined land and sea temperatures seen in the decadal means of Figure SPM.1 in the IPCC Summary for Policy Makers (IPCC SPM, 2013; see also Fig. S4) started in the 1980s.…”
Section: (G)supporting
confidence: 89%
“…Many statistical techniques exist to identify regime shifts (e.g. Beaugrand, 2004;Mantua, 2004;Rodionov & Overland, 2005;Rodionov, 2006;Beaulieu et al, 2012a;Varotsos et al, 2013). All have strengths and drawbacks, but the three we use here are complementary.…”
Section: Identification Of the 1980s Regime Shift In A Wide Range Of mentioning
confidence: 99%
“…Based on the analysis of 65 years (1951-2016) of continuous meteorological data, we can see that the annual average temperature increased at a rate of 0.114 • C/decade, and that the rate has accelerated since the 1990s. At the same time, we find that the temperature had a rapid shift in 1987, coinciding with the findings of Varotsos et al (2014) [21]. The annual precipitation decreased slowly at a rate of −33.22 mm/decade, showing a "warm-dry" trend.…”
Section: Habitat Suitability Under Climate Changesupporting
confidence: 85%
“…Furthermore, it has long been recognized that despite the slow and gradual climate variability, rapid climate changes might be expected, since the climate system is in an unstable equilibrium. In this context, Varotsos et al (2014) found that the increase in sea-surface temperature over 30 • S-60 • N from 1900 to 2012 did not occur slowly and gradually, but abruptly in 1925/1926 and 1987/1988 with events time-separated by 62 years, i.e., an interval reminiscent of the well-established quasi 60-year natural cycle [21]. Evidence for the quasi 60-year oscillation has also been found by Zhen-Shan and Xian (2007) and has been shown to be among the most prominent climate variability components of the annual mean temperature in China, the Northern Hemisphere, and globally in the period from 1881 to 2002 [22].…”
Section: Introductionmentioning
confidence: 99%
“…Complexities associated with meteorological and geophysics processes have been reviewed in Sharma et al (2012). Modelling complexity of atmospheric phenomena and generating prediction schemes accordingly has long been an area of major concentration for the meteorologists over the globe (Kondratyev and Varotsos, 1995;Varotsos 2005, 2013, Blackwell 2014Varotsos et al 2014a). In view of importance of the estimation of the future projected precipitation and rainfall on short-and long-term basis detrended fluctuation analysis has been implemented by Efstathiou and Varotsos (2012) in rainfall time series to explore the intrinsic properties of their temporal variability.…”
Section: Introductionmentioning
confidence: 99%